THE POETICS OF IGOR SEVERYANIN AND LITERARY PARODY AT THE BEGINNING OF THE 20 TH CENTURY - Ekaterina V. Kuznetsova (Studia Litterarum)
The article analyzes the specificity of the pre-emigrant work by Igor Severyanin and its poetics (absurdity, paradox, mixture of style, nonsense, and exaggeration) against the rapid development of popular literature at the turn of the 19 th and 20 th centuries and the rise of parodic genres in particular. Beginning his literary career, the young poet had to develop his own style deriving from the preceding generations of poets — elder and younger generations of Russian Symbolists. Most likely, his style developed as a conscious parody of Symbolist themes, images, masks, and stylistic devices. Critics (K. Mochulsky, W. Hovin, and О. Kushlina) already pointed at the overlaps between Severyanin and other Symbolists and featured parodic elements in the work of the former. The rapid development of the genre of literary parody in the Russian literature at the turn of 19 th and 20 th centuries was likely to inspire Severyanin to use parody techniques in his work. To prove this hypothesis, the essay compares Severyanin’s poems with those of his elder contemporaries, such as V. Bryusov and K. Bal’mont and with literary parodies by S. Gorny, K. Chukovsky, and A. Blok that were famous in the early 20 th century. I read some of Severyanin’s poems as hidden parodies or “ambiguous texts.” They are different from traditional parodies in that they may be perceived as serious and independent works in case the background knowledge about their literary context is lost and also depending on the reader’s individual viewpoint.